Device-to-Device (D2D) Communication Power Control for Interference Management in Existing Cellular Network - Muhammad Putra Pamungkas; Luluk Muthoharoh; Reni Permatasari (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2022)
The need for telecommunications access continues to increase. This is accompanied by the need for access to internet services. Within the increasing number of service users every time the improvement of quality of service is needed. jz power control method on the interference, used two schemes of power control method that is fixed power control, and adaptive power control. The result of simulation obtained by CDF analyisis scheme of fixed power control able to improve SINR equal to 11,45% and adaptive power control have value of improvement 8,65% in downlink period. And in uplink period increase of SINR equal to 3,29% with fixed power control and 2,24% with adaptive power control.